MECHANISMS, CHALLENGES AND IMPLICATIONS OF POLITICAL LEADERSHIP IN DEMOCRATIC COUNTRIES - Ulaya, Aqila Adwa (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This paper discusses leadership in the political sphere, focusing primarily on the understanding of political leadership concepts, the basis of legitimacy, the structure and functions of political leadership, as well as the succession process in democratic systems. The study adopts a literature review approach, involving the exploration of various sources, including academic books and relevant articles obtained through online research. The objective of this writing is to provide a comprehensive understanding of political leadership by referring to relevant theories, and to deepen insights into the dynamics of political leadership practices. Despite limitations in terms of sources and information, the author welcomes constructive feedback and suggestions from readers to improve the quality of this work. It is also hoped that this paper can serve as a useful reference for those interested in exploring political leadership, especially for individuals in society who aspire to become leaders in the future.